Fed up : emotional labor, women, and the way forward - Hartley, Gemma, 1988- (HarperOne, 2018)
"In her ultra-viral article 'Women Aren't Nags--We're Just Fed Up,' ... Gemma Hartley gave ... voice to the frustration and anger experienced by countless women. Now, in Fed Up, Hartley expands outward from the everyday frustrations of performing thankless emotional labor to illuminate how the expectation to do this work in all arenas--private and public--fuels gender inequality, limits our opportunities, steals our time, and adversely affects the quality of our lives"--Dust jacket flap.